Family practice records are in danger - Granja, Mónica (2018)
Medical records are a key element of health care delivery. Records written by Portuguese family physicians often contain incomplete baseline information, progressive replacement of clinical notes by items of the International Classification of Primary Care, problems that are not listed according to their highest level of resolution and lists of problems that are neither complete nor a rigorous clinical summary of the patient. Limitations of the software ‘SClínico Cuidados de Saúde Primários’ may explain these problems on medical records. This application is not compatible with the Problem-Oriented Medical Record; on the other hand, it forces the use of the International Classification of Primary Care before the entry of actual clinical notes. Imposed performance indicators may also be another possible explanation. Family physicians must persist in the quality of their records and take an active part in the development of electronic health record systems, keeping them centred on the patient and on health care delivery.